Management of lateral pelvic lymph nodes by Australasian colorectal surgeons: An insight from the west. Issue 6 (2nd March 2021) - Cribb, Benjamin; Kong, Joseph; Warrier, Satish; McCormick, Jacob; Heriot, Alexander
Abstract: Purpose: Lateral pelvic lymph node dissection (LPLND) for locally advanced low rectal cancer is a common practice in Japan. However, it is not widely performed in western countries. The aim of this survey study is to assess the current practice and management of lateral pelvic lymph nodes by colorectal surgeons in Australasia. Methods: The authors developed a survey to assess surgeons' assessment and management of lateral pelvic lymph nodes in patients with rectal cancer. The survey was run through the online RedCap® platform in 2019. An electronic link and request to complete the survey was sent to specialist surgeons of the Colorectal Surgical Society of Australia and New Zealand (CSSANZ). Results: Ninety‐two colorectal surgeons completed the online survey (32% response rate). Eighty percent of participants consider malignant lateral pelvic lymph nodes to represent locoregional and resectable disease. In patients with clinically malignant lateral pelvic lymph nodes on preoperative imaging the majority of respondents (92%) recommend neoadjuvant chemoradiotherapy and 86% would also recommend LPLND. Over half of the surgeons (57%) had no exposure to LPLND during fellowship training and approximately two thirds (62%) do not perform LPLND in their current practice. Conclusion: This study highlights the challenges in the management of the lateral pelvic lymph nodes in a western context. The majority of the participating Australasian colorectal surgeons consider malignant lateral pelvic lymph nodes to represent locoregional and resectable disease. The majority also recommend LPLND for clinically malignant lateral pelvic nodes. However, adequate training and experience with LPLND is limited.